The Effect Of Games-Based Problem Based Learning (PBL) Model On Literacy And Numeracy Of Class IV Students - Hamzah, Haswella; Syam, Nur; Irviana, Ira (ALENA : Journal of Elementary Education, 2025)
The Effect of Games-Based Problem Based Learning (PBL) Model on Literacy and Numeracy of Class IV Students of UPT SPF SD Inpres Layang III Makassar City. This study aims to determine the effect of the games-based Problem Based Learning (PBL) model on literacy and numeracy of grade IV UPT SPF SD Inpres Layang III Makassar City school year 2024 odd semester. This type of research is experimental research designs one-group pretest-posttest. With the subject of this study were 24 UPT SPF SD Inpres Layang III class IV students, of which 9 male students and 12 female. Data collection was carried out using interviews, observations, tests, and documentation. The data collected in the study were analyzed using descriptive and inferential analysis techniques. Based on the results of data analysis, the average literacy pre-test before treatment was 60.95 while after treatment was 80.48. And the numeracy pre-test before being given the treatment was 65.24 while after being given the treatment was 89.52. Hypothesis testing of the experimental class obtained normality test is 0.163 which means very effective. Based on the results of the study, there is an effect of the games-based Problem Based Learning (PBL) model on literacy and numeracy of class IV UPT SPF SD Inpres Layang III students.